2022
DOI: 10.1038/s41379-022-01080-0
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and clinical significance of atypical mitosis in breast cancer

Abstract: Atypical mitosis is considered a feature of malignancy, however, its significance in breast cancer (BC) remains elusive. Here, we aimed to assess the clinical value of atypical mitoses in BC and to explore their underlying molecular features. Atypical and typical mitotic figures were quantified and correlated with clinicopathological variables in a large cohort of primary BC tissue sections (n = 846) using digitalized hematoxylin and eosin whole-slide images (WSIs). In addition, atypical mitoses were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…In this study, a significant association was found between high PLK1 expression and high mitotic score, supporting a previous study findings 26 . This confirms the role of PLK1 in regulation of mitosis process and its function to ensure the correct execution by phosphorylating centromere protein A (CENPA) to promote its assembly during the metaphase‐anaphase transition in mitosis 5,49,50 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, a significant association was found between high PLK1 expression and high mitotic score, supporting a previous study findings 26 . This confirms the role of PLK1 in regulation of mitosis process and its function to ensure the correct execution by phosphorylating centromere protein A (CENPA) to promote its assembly during the metaphase‐anaphase transition in mitosis 5,49,50 …”
Section: Discussionsupporting
confidence: 91%
“…However, others found that knockdown of PLK1 inhibited ER expression and the PLK1 mRNA overexpression correlates with poor prognosis in luminal BC 24,25 . In a recent study, we found that PLK1 was significantly associated with atypical mitosis in BC 26 …”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Ki67 and mitotic index (MI) are indicators of tumour proliferation rate and both are significantly correlated 6. Analogous to Ki67, the advancing edge of the tumour, probably in the areas of highest mitotic counts, is likely to be representative of tumour clones that drive the biological potential of the tumour 26 69. Mitotic count, which can easily be assessed in a defined area on H&E-stained slides, represents the dividing cells, while Ki67 IHC represents the cells in the cell cycle.…”
Section: Ki67 Assessmentmentioning
confidence: 99%